The National Wealth Score in the Brazilian National Survey on Child Nutrition (ENANI-2019) - Pedro Gomes Andrade; Raquel Schincaglia; Dayana Rodrigues Farias; Inês Rugani Ribeiro de Castro; Luiz Antonio dos Anjos; Elisa Maria de Aquino Lacerda; Cristiano Siqueira Boccolini; Nadya Helena Alves-Santos; Paula Normando; Maiara Brusco de Freitas; Neilane Bertoni; Gilberto Kac (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2023)
The National Wealth Score (IEN) is a synthetic household index that assesses socioeconomic conditions. This study aims to present the methods used to update the IEN using data from the Brazilian National Survey on Child Nutrition (ENANI-2019). The following items were included: the education level of the mother or caregiver of the child; the number of bedrooms and bathrooms, TV sets, and cars in the household; and the presence of a radio, refrigerator or freezer, washing machine, microwave oven, telephone line, computers, air conditioner, media player devices, cable or satellite TV, cell phone ownership and type of service, cell phone internet, and internet at the household. Principal component analysis (PCA) was used to estimate the IEN with and without incorporating the complex sampling design (CSD). Thus, the IEN validation considered proxy indicators of socioeconomic status and living conditions. The first component of the PCA explained 31% and 71% of the variation with and without incorporating the CSD, respectively. The coefficients of variation of the IEN were 53.4% and 2.6% with and without incorporating the CSD, respectively. The mean IEN score was lower in households without access to a sewage system, those that received benefits from Brazilian Income Transfer Program, those with some degree of food insecurity, and those with stunted children. Adding ENANI-2019 items to the calculation of IEN to capture technological advances resulted in a better fit of the model. Incorporating the CSD increased PCA performance and the IEN precision. The new IEN has an adequate performance in determining the socioeconomic status of households with children aged under five years.